Activities of the youth parliament under the chambers of the Oliy Majlis and the role of political parties (Eurasian Research Bulletin, 2025)
This scientific article analyzes the activity of the Youth Parliament under the Chambers of the Oliy Majlis and the role of political parties in this process. The Youth Parliament is an important institution established to ensure the active participation of the youth of Uzbekistan in social and political life and to hear their opinions. The article examines in detail the main tasks, functions and interactions of the Youth Parliament with political parties. Political parties play an important role in encouraging the active participation of young people in political processes, involving them in politics through their platforms and increasing their activity in relation to social issues. Also, the article shows how the Youth Parliament, in cooperation with political parties, involves young people in political processes and expands their opportunities to express their opinions on social issues. Through this analysis, the article provides recommendations for improving the interaction between the youth parliament and political parties and developing democratic processes